DISEMINASI INFORMASI PROGRAM KERJA PEMERINTAH KOTA BEKASI MELALUI RADIO - VIVI OKTAVIANI; TATIK YUNIARTI (Institut Bisnis Muhammadiyah Bekasi, 2020)
Radio is a mass media that can be used to disseminate information. Nielsen Radio Audience Measurement noted that in the third quarter of 2017, 57% of the total radio listeners came from generation Z and millennials. This made the Bekasi City government collaborate with the localradio media to spread information related to the Bekasi City government's work program. The study was conducted to determine the information dissemination of Bekasi City government work programs via radio. The research method uses descriptive qualitative. The results showed that the dissemination of information on the Bekasi City government work program in order to realize development in Bekasi City was divided into four elements. First, sources in the dissemination of information on the work program of the Bekasi City government are delivered directly by speakers in accordance with their field expertise. Second, the delivery of messages is done through radio talkshows relating to the vision and mission of the City of Bekasi. Third, the Bekasi City government disseminatesinformation on the Bekasi City government work program through local radio media in Bekasi City, namely Dakta, Elgangga and Gaya radio by interactively opening via Phone, SMS, Whatsapp, Fanpage and Twitter to get responses from the community related to information dissemination and the development of Bekasi City government work programs. Fourth, the Bekasi City community as the recipient of the message during the talkshow can directly deliver criticisms and suggestions related to the work program of the Bekasi City government in accordance with communication skills, attitudes, knowledge, social and cultural systems that affect the Bekasi City community in receiving messages